Catalisadores a base de SrSnO3:Ni2+ não suportados e suportados para reação de redução de NO com CO - Souza, João Jarllys Nóbrega de (2012)
This work involved the synthesis of an oxide with perovskite structure (ABO3), the strontium stannate (SrSnO3), with orthorhombic structure, space group Pbnm, by the polymeric precursor method. This material has been applied as capacitor, sensor for gases as NO, CO, H2, humidity and it is actually being studied as a catalyst. At the beginning of this work, pure SrSnO3 and doped with 10 mol % of nickel (Sr0,9SnNi0,1O3, SrSn0,9Ni0,1O3, Sr0,95Sn0,95Ni0,1O3) were characterized by thermal analysis (TG / DTA), infrared spectroscopy (IR), Ultraviolet-visible spectroscopy (UV-Vis), Raman spectroscopy, X-ray diffraction and surface area by BET method. The catalytic activity of the non-supported material was evaluated in the reduction reaction of nitrogen monoxide (NO) by carbon monoxide (CO), followed by characterization by XRD, IR and Raman analysis. The material calcined at 800°C presented SrCO3 as secondary phase, with a reduction in its intensity when Ni2+ replaces Sr2+ in the lattice. Doping did not lead to a meaningful change in the long range order by increased the short range order. The system best catalytic performance (SrSn0,9Ni0,1O3) achieved approximately 90% of conversion of CO into CO2 and 85% of NO into N2. In the second part of the work catalysts were supported (10% mass, the active phase /support) on anatase, gamma alumina, ceria and zirconia, using the resin obtained by the polymeric precursor method, with characterization as described before. This procedure aimed at evaluating the effect of the support in the activity of perovskite for the same reaction conditions. It was possible to confirm the catalyst deposition on all supports, in spite of the difficulty in the characterization as a film was formed on the powder surface, leading to superposition of peaks/bands.